Pengaruh Technology Acceptance Factors, Website Service Quality, dan Specific Holdup Cost, Terhadap Loyalitas Pelanggan Pada Platform Shopee.Co.Id (Studi Pada Mahasiswa Politeknik Kotabaru) - Dayat Ikhsan Hajati (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2020)
The aims of this study were to analyze the significant and positive effect of technology acceptance factor, website service quality, specific holdup cost on customers’ loyalty partially and simultaneously. The population were Polytechnic of Kotabaru students with 95 people as the samples by purposive sampling technique. The method of data analysis used multiple linear regression. The results showed that 1) there was no significant effect technology acceptance factors on customers’ loyalty partially but has a positive effect, 2) there was negative and no significant effect website service quality on customers’ loyalty partially, 3) there was positive and significant effect specific holdup cost on customers’ loyalty partially, 4) there were positive and significant effect on technology acceptance factors, website service quality, specific holdup cost simultaneously.